2014
DOI: 10.1371/journal.pone.0104867
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Response of Musca domestica Larvae to Bacterial Infection

Abstract: The house fly Musca domestica, a cosmopolitan dipteran insect, is a significant vector for human and animal bacterial pathogens, but little is known about its immune response to these pathogens. To address this issue, we inoculated the larvae with a mixture of Escherichia coli and Staphylococcus aureus and profiled the transcriptome 6, 24, and 48 h thereafter. Many genes known to controlling innate immunity in insects were induced following infection, including genes encoding pattern recognition proteins (PGRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 57 publications
(68 reference statements)
5
26
2
Order By: Relevance
“…Our current findings are consistent with previous reports on the upregulation of genes involved in innate immunity against invading bacteria in Musca domestica larvae (27). We speculate that the induction of antimicrobial activity was mediated by imd as well as Toll pathway, which were essential innate immune responses in Drosophila (1).…”
Section: Characterization Of the Induced Antimicrobial Activity Of Hesupporting
confidence: 93%
“…Our current findings are consistent with previous reports on the upregulation of genes involved in innate immunity against invading bacteria in Musca domestica larvae (27). We speculate that the induction of antimicrobial activity was mediated by imd as well as Toll pathway, which were essential innate immune responses in Drosophila (1).…”
Section: Characterization Of the Induced Antimicrobial Activity Of Hesupporting
confidence: 93%
“…In 2014, the genome of M. domestica was decoded by Scott et al (2014), which will increase the understanding of housefly's adaptation to septic environments. We also finished a transcriptome research targeting housefly's response to bacterial challenge (Tang et al, 2014), and found that various components of the Toll and Imd signaling pathways were induced after bacterial infection. We designed this study to track the role of housefly PGRP-SC in Imd pathway and developmental process, expecting to see PGRP-SC's function in the innate immunity system from an evolutionary angle.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have indicated that AMPs from the housefly possess pharmacological value (Cao et al, ; Chen et al, ). Using high‐throughput sequencing methods, seven AMP genes ( CECROPIN, ATTACIN, DEFENSIN, DIPTERICIN, MUSCIN, DOMESTICIN, and LYSOZYME ) have been found in M. domestica infected with a mixture of E. coli and S. aureus (Tang et al, ). In the present study, LC‐MS/MS analysis revealed seven AMPs families in Md ‐AMPs.…”
Section: Discussionmentioning
confidence: 99%